Analisis Pengaruh Gaya Gesek Pada Pergerakan Benda Dengan Melalui Simulasi Phet - Galuh Kinanthi Dwinka Raharjo Raharjo; Bagas Eka Firmansyah; Muhammad Nur Hadi (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2025)
This study aims to analyze the effect of force on the motion of objects by utilizing PhET Interactive Simulations. The main focus of the study is to examine the relationship between frictional force and mass on changes in object velocity and acceleration. The method used is a simulation-based experimental method, in which the applied force and friction coefficient are changed gradually to observe the object’s motion response. The collected data include the magnitude of frictional force, resultant force, acceleration, and graphs of the relationship between force and velocity. The results of the study show that an increase in the applied force produces greater acceleration as long as the frictional force does not exceed the applied force. In addition, a higher friction coefficient causes the object to be more difficult to move and reduces acceleration. PhET simulations are proven to be effective as a visualization medium for force concepts because they provide direct understanding of the relationships among motion dynamics variables. This study can serve as an alternative technology-based physics learning approach to support students’ understanding of force concepts. The method used in this study is a simulation-based experimental method, in which the applied force and friction coefficient are changed gradually and systematically to observe the object’s motion response. The simulation allows direct observation of motion changes without the limitations of real laboratory equipment. The collected data include the magnitude of frictional force, resultant force, acceleration values, and graphs of the relationship between force and object velocity. The results show that an increase in the applied force produces greater acceleration as long as the frictional force acting does not exceed the applied force. Conversely, an increase in the friction coefficient causes the object to become more difficult to move and reduces acceleration. These findings show a clear relationship between force, mass, and acceleration in accordance with Newton’s laws. PhET simulations are proven to be effective as a visualization medium for force concepts because they help learners understand the relationships among variables in a more concrete, interactive, and meaningful way. Therefore, this study can be used as an alternative technology-based physics learning approach to improve understanding of force concepts and motion dynamics.